Artificial intelligence for controlling the operational efficiency of metallurgical enterprises: a review of modern approaches, technologies, and challenges - Detyuk, S. V.; Koyfman, O. O.; Детюк, С. В.; Койфман, О. О. (ТОВ «ТЕХНІЧНИЙ УНІВЕРСИТЕТ «МЕТІНВЕСТ ПОЛІТЕХНІКА», 2025)
This study is dedicated to examining the transformational potential of artificial intelligence (AI) and, in particular, large language models (LLMs) in controlling the operational efficiency of metallurgical enterprises. It examines contemporary approaches, advanced technologies, and key challenges associated with integrating AI into such critical areas as automated manufacturing process management, quality control, predictive maintenance, supply chain management, and workforce management. Based on a comprehensive literature analysis, this article elucidates how LLMs can enhance efficiency, accuracy, and adaptability within the metallurgical industry, and it also identifies gaps in existing research that warrant further investigation.The integration of AI and LLMs in the metallurgical industry faces complex challenges such as the specificity of industry data and terminology, the opacity of “black box” algorithms, insufficient adaptation of models to industrial conditions, high computational demands, and real-time issues. Additionally, there is a need for qualified personnel, cultural changes, and the development of service staff.A comprehensive approach for the successful implementation of AI technologies in the management of the operational activities of a metallurgical enterprise will include targeted research that takes into account practical, economic, and social aspects. The key directions are the development of physics-informed AI with the integration of metallurgical knowledge, the creation of hybrid systems combining LLMs with traditional methods, and the application of unsupervised learning to overcome data scarcity. The priority is to enhance the interpretability of models, integrate with Digital Twins for real-time monitoring, embed safety constraints through predictive control models, and fine-tune universal LLMs for metallurgical applications.

Дослідження присвячено вивченню трансформаційного потенціалу штучного інтелекту (ШІ) та, зокре-ма, великих мовних моделей (ВММ) в управлінні ефективністю операційної діяльності металургійних під-приємств. Розглядаються сучасні підходи, передові технології та основні виклики, пов’язані з інтеграці-єю ШІ в такі критично важливі сфери, як автоматизоване управління виробничими процесами, контроль якості, прогнозне обслуговування, управління ланцюгами постачання та кадровий менеджмент. На основі всебічного аналізу літератури висвітлено, як ВММ можуть підвищити ефективність, точність і адап-тивність металургійної промисловості, а також ідентифіковано прогалини в наявних дослідженнях, що потребують подальшого вивчення.Інтеграція ШІ та ВММ-моделей у металургійній промисловості стикається з такими комплексними викликами, як специфічність галузевих даних і термінології, непрозорість алгоритмів «чорного ящика», недостатня адаптація моделей до промислових умов, високі обчислювальні вимоги та проблеми реально-го часу. Додатково виникають потреба в кваліфікованих кадрах, культурні зміни та розвиток обслугову-ючого персоналу.Комплексний підхід для успішного впровадження ШІ-технологій в управлінні операційною діяльністю металургійного підприємства буде включати цілеспрямовані дослідження, що враховують практичні, еко-номічні та соціальні аспекти. Ключовими напрямами є розвиток фізично-інформованого ШІ з інтеграцією металургійних знань, створення гібридних систем поєднання ВММ із традиційними методами, застосу вання неконтрольованого навчання для подолання дефіциту даних. Пріоритетним є підвищення інтерпре-тованості моделей, інтеграція із цифровими двійниками для моніторингу реального часу, вбудовування обмежень безпеки через прогнозні контрольні моделі та доналаштування універсальних ВММ для мета-лургійних застосувань.
Штучний інтелект для управління ефективністю операційної діяльності металургійного підприємства: огляд сучасних підходів, технологій та викликів
Keywords: Artificial Intelligence; Large Language Models; Metallurgical Industry; Operational Activity; Digital Twins; Predictive Maintenance; Quality Control; Management; штучний інтелект; великі мовні моделі; металургійна промисловість; операційна діяльність; цифрові двійники; прогнозне обслуговування; контроль якості; управління